Ibetazol, a novel inhibitor of importin β1-mediated nuclear import - Thomas Vercruysse; Els Vanstreels; Maarten Jacquemyn; Sandro Boland; Amuri Kilonda; Sara Allasia; Ilse Vandecaetsbeek; Hugo Klaassen; Matthias Versele; Patrick Chaltin; Arnaud Marchand; Dirk Daelemans (Communications Biology)
Abstract Nucleocytoplasmatic transport plays an essential role in eukaryotic cell homeostasis and is mediated by karyopherins. Importin β1 (KPNB1) and its adaptor protein importin α1 (KPNA2) are the best-characterized karyopherins that effect nuclear import. Here, we identify a novel small-molecule inhibitor of the importin β1-mediated nuclear import. We design a reporter cell line by stably tagging endogenous importin α1 with a fluorescent protein to screen for compounds affecting its subcellular localization. We identify a series of compounds that trigger cytoplasmatic accumulation of importin α1. The lead compound, ibetazol, is further characterized in a broad sequence of cellular nuclear transport assays. Ibetazol is shown to inhibit all importin β1-mediated nuclear import quickly and specifically, without affecting transport mediated by other karyopherins. Detailed molecular mechanism of action studies demonstrate that ibetazol inhibits importin β1 by covalently targeting Cys585. In summary, ibetazol is a novel small molecule inhibitor of importin β1 enabling pharmacological inhibition of the importin β1-mediated nuclear import process with wide applicability in different fields.